Strategies to Produce Grapefruit-Like Citrus Varieties With a Low Furanocoumarin Content and Distinctive Flavonoid Profiles - Garcia-Lor, A.; Bermejo, A.; Morales, J.; Hernández, M.; Medina, A.; Cuenca, J.; Navarro, L.; Aleza, Pablo (Frontiers in Plant Science, 2021)
Pummelos and hybrids, such as grapefruits, have high furanocoumarin and low flavonoid contents. Furanocoumarins interact negatively with certain drugs, while flavonoids are antioxidant compounds with health benefits. To obtain new grapefruit-like varieties with low furanocoumarin and high flavonoid contents, diploid and triploid hybrid populations from crosses between diploid and tetraploid Clemenules clementine and diploid Pink pummelo were recovered and analyzed. With regard to furanocoumarins, triploids produce less bergapten, bergamottin and 6,7-DHB than diploids. Regarding flavonoids, triploids yielded more eriocitrin, narirutin, hesperidin and neohesperidin than diploids, whereas no differences were observed in neoeriocitrin and naringin. These results indicate that, the strategy to recover triploid hybrids by 4x x 2x crosses is more appropriate than the recovery of diploid hybrids by 2x x 2x crosses for obtaining grapefruit-like varieties of citrus with lower furanocoumarin and higher flavonoid contents.